Voriconazole in Prevention and Treatment of Febrile Neutropenia - Hamidreza Taghva Masoumi; Molouk Hajibabaie; Kheirollah Gholami; Maryam Shahrokhi (Research Center for Rational Use of Drugs (RCRUD), 2018)
Invasive fungal infections are one of important complication in patients receiving chemotherapy or hematopoietic stem cell transplantation. Voriconazole is a triazole antifungal agent widely used for prophylaxis and treatment of fungal infections. It is also administered for empiric treatment of fungal infections in patients with febrile neutropenia. Although amphotericin B preparations and fluconazole generally are used for empiric antifungal therapy and antifungal prophylaxis, but it should be noted that there are insufficient data to draw any firm conclusion about use of other new alternatives as drug of choice. This paper will review the researches that conducted on voriconazole as an empiric antifungal therapy or antifungal prophylaxis in patients with neutropenia following chemotherapy or HSCT.